What Caused My Cancer? Cancer Patients' Perceptions on What May Have Contributed to the Development of Their Cancer: A Cross-Sectional, Cross-Country Comparison Study. (23rd July 2019) - Hall, Alix; Nguyen, Sang Minh; Mackenzie, Lisa; Sanson-Fisher, Rob; Olver, Ian; Thuan, Tran Van; Huong, Tran Thanh
Accurate public perceptions on the risk factors associated with cancer are important in promoting primary, secondary, and tertiary prevention. Limited studies have explored this topic among patients with cancer in non-western, low-to-middle-income countries. A cross-sectional survey to compare Australian and Vietnamese cancer patients' perceptions of what caused their cancer was undertaken. Adult, patients with cancer from both countries, receiving radiotherapy treatment completed a standardized survey, which included a 25-item module assessing their beliefs on the causes of their cancer. Items ranged from known evidence-based causes (eg, smoking, sun exposure) to non-evidence-based beliefs (eg, stress or anxiety, physical injury, or trauma). Country-specific logistic regression analyses were conducted to identify differences in the determinants of patients' top perceived causes. A total of 585 patient surveys were completed (75% response rate; 285 from Australia, and 300 from Vietnam). Most patients were male (58%) and aged 60 years and older (55%). The most frequently reported risk factor overall and for the Australian sample was "getting older" (overall = 42%, Australia = 49%, and Vietnam = 35%). While the most frequently reported risk factor for the Vietnamese sample was "poor diet" (overall = 39%, Australia = 11%, and Vietnam = 64%). There were differences in the characteristics associated with the top causes of cancer identified by Australian and Vietnamese patients. Patients' beliefs about what may have caused their cancer are complex and likely to be impacted by multiple factors, including the country from which they reside. Developing public awareness campaigns that are accurate and tailored to address the specific beliefs and possible misconceptions held by the target community are needed.